Bell’s palsy misdiagnosis: characteristics of occult tumors causing facial paralysis - Eun-Jae Chung; Damir Matic; Kevin Fung; S. Danielle MacNeil; Anthony C. Nichols; Ruba Kiwan; KengYeow Tay; John Yoo (Journal of Otolaryngology - Head and Neck Surgery)
Abstract Objective The aim of this study was to report the incidence and clinical course of a series of patients who were misdiagnosed with Bell’s palsy and were eventually proven to have occult neoplasms. Methods Two hundred forty patients with unilateral facial paralysis who were assessed at the facial nerve reanimation clinic, Victoria Hospital, London Health Science Centre, from 2008 through 2017 were reviewed. Persistent paralysis without recovery was the presenting complaint. Results Nine patients (3.8%) who were proven to have occult neoplasms initially presented with a diagnosis of Bell’s palsy. The mean diagnostic delay was 43.5 months. Four patients were proven to have skin cancers, 3 patients had parotid cancers, and 2 patients had facial nerve schwannomas as a final diagnosis. Initial magnetic resonance imaging (MRI) was performed in all 9 patients and 8 underwent a follow-up MRI. An occult tumor was identified upon review of the original MRI in one patient and at follow-up MRI in 8 patients. The mean time interval between the initial and follow-up imaging was 30.8 months. The disease status at most recent follow-up were no evidence of disease in 2 patients (22%) and alive with disease in 7 patients (78%). An irreversible, progressive pattern of facial paralysis combined with pain, multiple cranial neuropathies or history of skin cancer were predictable risk factors for occult tumors. Seven out of the 9 patients (77.8%) underwent at least one type of facial reanimation surgery, and the final subjective results by the surgeon were available for 5 patients. Three out of the 5 (60%) patients who were available for final subjective analysis were reported as Grade III according to the modified House-Brackmann scale. Conclusion Occult facial nerve neoplasm should be suspected in patients with progressive and irreversible facial paralysis but the diagnosis may only become evident with follow-up imaging. Facial reanimation surgery is a satisfactory option for these patients. Graphical abstract